Sleep Problems Influence Emotional/Behavioral Symptoms and Repetitive Behavior in Preschool-Aged Children With Autism Spectrum Disorder in the Unique Social Context of China - Kang, Yu-Qi; Song, Xiao-Rong; Wang, Geng-Fu; Su, Yuan-Yuan; Li, Pei-Ying; Zhang, Xin (Frontiers in Psychiatry, 2020)
Sleep disturbances are common in people with autism spectrum disorder (ASD), but research on this topic is still limited in China. In the current study, we evaluated the prevalence of sleep problems in preschool-aged children with ASD and to examine the correlations between sleep disturbances and emotional/behavioral symptoms and repetitive behavior in the unique social context of China. This study recruited 475 preschool-aged children aged 3 to 6 years old, including 252 children with ASD (mean age 5.13±1.15, 80.6% male) and 223 age-matched typically developing (TD) children (mean age 5.12±0.97, 74.9% male). The parents of all children completed a sociodemographic questionnaire and the Childhood Sleep Habits Questionnaire. The parents of 114 ASD children completed the Strengths and Difficulties Questionnaire (SDQ) and the Repetitive Behavioral Questionnaire-2 (RBQ-2). The prevalence of sleep problems in preschool-aged children with ASD in this study was 81.7%, which was higher than that in TD children (61.0%). The scores for bedtime resistance, sleep anxiety, sleep duration, parasomnias, and sleep onset delay in the ASD group were significantly higher than those in the TD group (t=-7.664, P=0.000; t=-10.477, P=0.000; t=-4.133, P=0.000; Z=-3.916, P=0.000; Z=-7.093, P=0.000; respectively). Sleep onset delay explained 17.3% of the variance (adjusted R2=0.173) in the total SDQ score of children with ASD, and bedtime resistance explained a large proportion of total RBQ-2 score variance (adjusted R2=0.206). The high rate of sleep disturbances in preschool-aged children with ASD emphasizes the importance of screening for sleep problems in this population. Attention should also be directed toward formulating good sleep hygiene practices for preschool-aged children in the particular social context and cultural setting of China.